The Economic Impact of Community-Based Allied Health on the Acute Sector: A Systematic Review of Economic Evaluations - Tian EJ; Kumar S; Martin P; Ingram LA; Pham CT (Journal of Multidisciplinary Healthcare)
Esther Jie Tian,1 Saravana Kumar,1 Priya Martin,2 Lewis A Ingram,3 Clarabelle T Pham4 1Innovation, IMPlementation and Clinical Translation (IIMPACT) in Health, Allied Health and Human Performance, University of South Australia, Adelaide, South Australia, Australia; 2School of Health and Medical Sciences, University of Southern Queensland, Toowoomba, Queensland, Australia; 3Alliance for Research in Exercise, Nutrition and Activity (ARENA), Allied Health and Human Performance, University of South Australia, Adelaide, South Australia, Australia; 4College of Medicine and Public Health, Flinders Health and Medical Research Institute, Flinders University, Bedford Park, South Australia, AustraliaCorrespondence: Esther Jie Tian, UniSA Allied Health and Human Performance, University of South Australia, GPO Box 2471, Adelaide, South Australia, 5001, Australia, Tel +61883021300, Email jie.tian@mymail.unisa.edu.auAbstract: Community-based allied health (AH) services have previously demonstrated a potential positive impact on acute care utilization, with wide acceptance among consumers. However, little is known about their economic impact. This systematic review aimed to address this gap. The primary outcomes of interest included: (a) costs of at least one type of acute care utilization; and (b) cost-effectiveness regarding acute care. The secondary outcomes of interest included total healthcare and/or non-healthcare costs. An a priori protocol was registered with PROSPERO [CRD42023437013]. Inclusion criteria were: (a) stand-alone interventions led by practitioners/graduates from one or more target AH professions; (b) reported acute care utilization costs as a primary or secondary outcome; (c) full or partial economic evaluations; and (d) studies published in English from 2010 onward. Eligible studies were identified from relevant bibliographic databases and gray literature search (September and October 2023). Modified McMaster Critical Appraisal Tool for quantitative studies, McGill Mixed Methods Appraisal Tool, and Consensus on Health Economic Criteria List were used to assess methodological quality. Narrative synthesis and cost-effectiveness planes were used for synthesizing and presenting the findings. Twelve studies, comprising eight cost analyses and four full economic evaluations, were included. Both single disciplinary (led by physiotherapists, dietitians, social workers, or exercise physiologists) and multidisciplinary (involved two to five AH professions) services were identified. Collectively, ten studies showed cost savings in acute care, while seven indicated varying degrees of cost-effectiveness and cost savings in total healthcare and non-healthcare, from pre-post and between-group comparisons. The findings demonstrated trends towards economic benefits of AH, highlighting their potential to alleviate the pressures on the acute sector and even the wider health system. However, the evidence is limited and of lower quality, emphasizing cautious interpretation. This review underscores the value of AH services and highlights key areas requiring action to strengthen the evidence base.Keywords: allied health occupations, primary health care, community health services, costs and cost analysis